(untitled) (Minerva, 2019)
G.B.’s Commentaries on Seneca’s Letters provide a remarkable example of early literary criticism and throw some light on the evolutionary theory of growing Renaissance culture and teaching method in Northern Italy. Written in the first years of the XVth. century, the Commentaries share an outlasting Scholastic method of organization and focus on moral training arising from the text with a new awareness of linguistic techniques, literary style and historical concerns applied to every passage commented. Ms. 12 of Salamanca’s Library can help to clarify the work’s date of writing as well as to decide how many times Barzizza tried to improve his school notes on Seneca’s Letters to Lucilius.